Dulaglutide and renal outcomes in type 2 diabetes: an exploratory analysis of the REWIND randomised, placebo-controlled trial. Issue 10193 (13th July 2019) - Gerstein, Hertzel C; Colhoun, Helen M; Dagenais, Gilles R; Diaz, Rafael; Lakshmanan, Mark; Pais, Prem; Probstfield, Jeffrey; Botros, Fady T; Riddle, Matthew C; Rydén, Lars; Xavier, Denis; Atisso, Charles Messan; et al.
Summary: Background: Two glucagon-like peptide-1 (GLP-1) receptor agonists reduced renal outcomes in people with type 2 diabetes at risk for cardiovascular disease. We assessed the long-term effect of the GLP-1 receptor agonist dulaglutide on renal outcomes in an exploratory analysis of the REWIND trial of the effect of dulaglutide on cardiovascular disease. Methods: REWIND was a multicentre, randomised, double-blind, placebo-controlled trial at 371 sites in 24 countries. Men and women aged at least 50 years with type 2 diabetes who had either a previous cardiovascular event or cardiovascular risk factors were randomly assigned (1:1) to either weekly subcutaneous injection of dulaglutide (1·5 mg) or placebo and followed up at least every 6 months for outcomes. Urinary albumin-to-creatinine ratios (UACRs) and estimated glomerular filtration rates (eGFRs) were estimated from urine and serum values measured in local laboratories every 12 months. The primary outcome (first occurrence of the composite endpoint of non-fatal myocardial infarction, non-fatal stroke, or death from cardiovascular causes), secondary outcomes (including a composite microvascular outcome), and safety outcomes of this trial have been reported elsewhere. In this exploratory analysis, we investigate the renal component of the composite microvascular outcome, defined as the first occurrence of new macroalbuminuria (UACR >33·9 mg/mmol), a sustained decline in eGFR of 30% or more from baseline, or chronic renal replacement therapy. Analyses were by intention to treat. This trial is registered with ClinicalTrials.gov, number NCT01394952 . Findings: Between Aug 18, 2011, and Aug 14, 2013, 9901 participants were enrolled and randomly assigned to receive dulaglutide (n=4949) or placebo (n=4952). At baseline, 791 (7·9%) had macroalbuminuria and mean eGFR was 76·9 mL/min per 1·73 m 2 (SD 22·7). During a median follow-up of 5·4 years (IQR 5·1–5·9) comprising 51 820 person-years, the renal outcome developed in 848 (17·1%) participants at an incidence rate of 3·5 per 100 person-years in the dulaglutide group and in 970 (19·6%) participants at an incidence rate of 4·1 per 100 person-years in the placebo group (hazard ratio [HR] 0·85, 95% CI 0·77–0·93; p=0·0004). The clearest effect was for new macroalbuminuria (HR 0·77, 95% CI 0·68–0·87; p<0·0001), with HRs of 0·89 (0·78–1·01; p=0·066) for sustained decline in eGFR of 30% or more and 0·75 (0·39–1·44; p=0·39) for chronic renal replacement therapy. Interpretation: Long-term use of dulaglutide was associated with reduced composite renal outcomes in people with type 2 diabetes. Funding: Eli Lilly and Company.